CHEWING LICE (INSECTA: PHTHIRAPTERA) INFESTATION ON NATIVE DUCK (ANAS PLATYRHYNCHOS DOMESTICUS, LINN.) IN TAMIL NADU - N. Jeyathilakan; D. Basheer Ahamad; B. Dhivya; J. Selvaraj (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Lice infestation is one of the major problems to the duck farming, causing irritation that lead to lowered feed intake, retarded growth, reduced weight gain and decreased egg production. The present communication deals with occurrence of different species of lice in a desi duck from Cauvery delta region of Tamil Nadu. A farmer from Thanjavur district of Tamil Nadu brought five dead two year old native ducks for necropsy at Dept. of Veterinary Pathology, Veterinary College and research Institute, Orathanadu, Tamil Nadu. External examination of ducks revealed presence of 13 lice specimen in one bird. They were examined and identified as Trinoton querquedulae (n= 8), Anatoecus dentatus (n= 4) and Anaticola crassicornis (n= 1) morphologically. This study is the first to establish the presence of mixed lice infestation in native ducks from Cauvery delta region of Tamil Nadu and also first repot of Trinoton querquedulae in ducks from India.